2018
DOI: 10.1016/j.bbrep.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ShcD and RET interaction in neuroblastoma survival and migration

Abstract: Preliminary screening data showed that the ShcD adaptor protein associates with the proto-oncogene RET receptor tyrosine kinase. In the present study, we aimed to investigate the molecular interaction between ShcD and RET in human neuroblastoma cells and study the functional impact of this interaction. We were able to show that ShcD immunoprecipitated with RET from SK-N-AS neuroblastoma cell lysates upon GDNF treatment. This result was validated by ShcD-RET co-localization, which was visualized using a fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In 2007, ShcD was first identified as a positive regulator to melanoma cell migration as well as it was found to be upregulated in 50% of invasive and metastatic melanomas (3). Since then, few studies experimented the role of ShcD in cell migration (12,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, ShcD was first identified as a positive regulator to melanoma cell migration as well as it was found to be upregulated in 50% of invasive and metastatic melanomas (3). Since then, few studies experimented the role of ShcD in cell migration (12,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, Iwamoto et al [50] reported neuroblastoma development in a transgenic mouse that carried the RET oncogene driven by a mouse metallothionein regulatory element. Additional reports using cell lines support a role for GDNF/RET signaling in differentiation, migration, and metastasis [51][52][53][54][55][56]. Recently, using neuroblastoma models carrying activating Alk mutations in the context of MYCN overexpression, Cazes et al [57] demonstrated that RET is upregulated in an ALK-dependent fashion.…”
Section: Retmentioning
confidence: 98%
“…Binding of RET to the specific soluble ligand, glial-derived neurotrophic factor (GDNF), is very efficacious in activating pathways that are important for regulating enzymes or those which affect cell proliferation, differentiation, migration, and survival. As a result, overexpression of RET will end in tumor progression and metastasis in NB (Mabruk, Ahmed, Thomas, & Prigent, 2018). This provides a wide spectrum to investigate drugs that are helpful in this situation.…”
Section: Retmentioning
confidence: 99%